2017
DOI: 10.1080/00365513.2017.1402127
|View full text |Cite
|
Sign up to set email alerts
|

Cholestatic liver injury as a side-effect of dabigatran and the use of coagulation tests in dabigatran intoxication and after reversal by idarucizumab in bleeding and sepsis

Abstract: Idarucizumab, an antidote specific for dabigatran, became available recently. Dabigatran is not associated with increased risk of hepatotoxicity in comparison with warfarin, but it is seen as a rare side-effect. Cases of cholestatic liver injury due to dabigatran have not been reported previously. We present a case of severe gastro-intestinal bleeding with underlying dabigatran intoxication in a patient with renal failure and the effect of reversal of dabigatran using idaruzicumab on coagulation assays. Intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The other advantages of this method are that it is inexpensive, practical, simple, rapid, and suitable for routine use 10. Recent studies have reported that impaired TDB is associated with various disorders such as diabetes mellitus11, myocardial infarction12, familial Mediterranean fever13, and cancer 14. However, to our knowledge, TDB as an index of oxidative stress in children with β-TM has not been investigated by using a newly developed method.…”
Section: Introductionmentioning
confidence: 99%
“…The other advantages of this method are that it is inexpensive, practical, simple, rapid, and suitable for routine use 10. Recent studies have reported that impaired TDB is associated with various disorders such as diabetes mellitus11, myocardial infarction12, familial Mediterranean fever13, and cancer 14. However, to our knowledge, TDB as an index of oxidative stress in children with β-TM has not been investigated by using a newly developed method.…”
Section: Introductionmentioning
confidence: 99%
“…Overdose resulting from DOAC self‐ingestion has been poorly reported, mostly as single cases, limited series and PCC reports, representing ~100 cases, with serum/plasma concentration assessment in <20 cases (Table 3). 12–35 Overall, suicidal ingestion does not seem to result in notable bleeding despite high‐ingested amounts and high peak plasma concentrations in most patients. Of note, peak DOAC concentrations in patients included in clinical trials evaluating DOAC for stroke prevention in atrial fibrillation or venous thromboembolism treatment (ie at regular doses) showed a wide inter‐individual variability 3,36 .…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 29 additional cases mostly involving intentional exposure to dabigatran ( n = 15), rivaroxaban ( n = 8) and apixaban ( n = 6) were published (Table 3). 12–35 Only 10 of these 29 cases presented bleeding. A 53‐year‐old man who co‐ingested 200 mg apixaban presented minor oozing from his femoral venous line insertion site, easily controlled with direct pressure and prothrombin complex concentrate 13 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the peak value of anti-FIIa was significantly correlated with bleeding events, indicating that anti-FIIa activity is more worthy of clinical attention than the other PD indicators. Relevant studies also showed that patients with high peak values of PD indicators such as APTT experienced significantly more bleeding events ( 30 ). Nevertheless, the trough value is more related to the bleeding risk than the peak value ( 31 ).…”
Section: Discussionmentioning
confidence: 99%